Association of social determinants of health and their cumulative inequities with risk of hypertension: a population-based study - Shao, Jinhai; Sun, Zhichao; Fang, Yong; Song, Bowen; Shou, Zhongyi; Cao, Guangli (Frontiers in Cardiovascular Medicine, 2025)
BackgroundHypertension remains a global public health challenge with significant socioeconomic disparities. While traditional risk factors are well-documented, the cumulative impact of adverse social determinants of health (SDoH) on hypertension risk warrants further investigation.MethodsWe analyzed data from 36,836 NHANES participants (2005–2018), including 15,082 hypertension cases. Eight SDoH indicators across five domains (economic stability, education, healthcare access, neighborhood environment, and social context) were evaluated using survey-weighted multivariable logistic regression. Primary models adjusted for age, sex, and race with subsequent stratified analyses by sex. Sensitivity analyses further adjusted for clinical covariates including BMI, smoking status, and comorbidities. Additionally, mediation analysis was performed to explore whether depression served as a psychosocial mediator in the association between adverse SDoH and hypertension risk.ResultsFive adverse SDoH showed significant associations with hypertension risk: unemployment (AOR = 1.27, 95%CI: 1.17–1.37), low poverty-income ratio (AOR = 1.20, 95%CI: 1.10–1.31), food insecurity (AOR = 1.25, 95%CI: 1.14–1.36), low education level (AOR = 1.09, 95%CI: 1.03–1.17), and government or no insurance (AOR = 1.08, 95%CI: 1.01–1.15). A clear dose-response relationship emerged, with each additional adverse SDoH increasing hypertension risk (1 factor: AOR = 1.19; 5 factors: AOR = 1.46; P-trend < 0.0001). Sex differences were notable, with unemployment more strongly associated in men (AOR = 1.39) and low income more impactful in women (AOR = 1.40). Mediation analysis revealed that depression partially mediated the effects of several adverse SDoH on hypertension, accounting for approximately 9%–13% of the total association.ConclusionAdverse SDoH were found to be associated with increased hypertension risk in a cross-sectional analysis, with distinct sex-specific and psychosocial pathways. The partial mediation effect of depression suggests that mental health may play a significant role in linking social disadvantage to hypertension, underscoring the importance of integrating psychosocial considerations into hypertension prevention and management.